Peningkatan Hasil Belajar Siswa dalam Pembelajaran PKN dengan Model NHT di SD Kartika 1-11 Padang - Asnul Rahman (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This research aimed at describing the improvement of students’ learning outcome by using cooperative learning model with Numbered Head Together type at SD Kartika 1-11 Padang. This research used both qualitative and quantitative approaches.The subject of this research was a teacher as researcher, and students. The result of the research revealed that there was an improvement in civic education learning based on the evaluation of lesson plan, the observation of the students and teacher’s activities, and the students’ learning outcome. It was found that the students’ learning outcome in cycle I was 70.38, and it was improved to 87.38 in cycle II.